Pemanfaatan Produk Reject menjadi Bahan Baku Melalui Filtrasi dan Agitasi Sebagai Efisiensi Proses Produksi Sorbitol Powder - Hidayat, Taufiq; Qadariyah, Lailatul; Kristianto, Teguh (Prosiding Sains dan Teknologi, 2024)
The Sorbitol Powder Plant (SPP) Department at PT Sorini Towa Berlian Corporindo is a manufacturer of Sorbitol powder using Sorbitol LTS (Low Total Sugar) raw material produced by the Sorbitol Liquid Plant (SLP) Department. SPP faces significant issues regarding the reject product rate, especially at the Pulse Air Collector (PAC) reject product outlet. Currently, the rejected products are only remelted and returned to SLP for reprocessing due to their high contamination levels, as confirmed by quality testing results. This research aims to find a solution to utilize the rejected products from PAC 18 and PAC 26 as raw materials. The methods applied in this research are Filtration and Agitation. The research results indicate that product contamination can be minimized. The findings from the research are then implemented in a project to reduce raw material consumption and improve production efficiency in the SPP department.